Critical reading of medical evidence: How to read observational studies? - Barboza, Joshuan J. (2021)
Objetive. The critical reading of scientific articles allows the medical community, above all, to improve the context of decision making. The great amount of scientific production worldwide makes use of observational studies, however, a significant proportion is not useful for decision making, not because of its methodological limitations but because of errors in its application. Many studies published in relation to coronavirus 2019 disease have limitations and require statistical, epidemiological and clinical tools to be able to assess them and incorporate them into the practice of evidence-based medicine. In this review, we analyze the different observational research designs and with the help of examples we will see the different steps in the research process.